Innovation by knowledge exploration and exploitation: An empirical study of the automotive industry - Gonzalez, Rodrigo Valio Dominguez; De Melo, Tatiana Massaroli [UNESP] (FapUNIFESP (SciELO), 2018)
In face of dynamic environment, such as the automotive sector, organizations are challenged to establish strategic flexibility through innovations, which require knowledge exploration and exploitation. Previous studies point out that the combination of knowledge exploration and exploitation is the ideal strategy for innovation since it will lead organizations to access new technologies and refine and improve the dominant technology through the exploitation of primary knowledge. Most studies on the subject focus their contributions on analyzing the impact of knowledge management initiatives and the knowledge exploration and exploitation on the company's innovative and financial performance; however, few studies have investigated the organizational factors that sustain the knowledge exploration and exploitation. The research results show that the processes of exploration and exploitation are impacted differently by five contextual factors considered in this research (human resource management, collaborative leadership, learning culture, autonomy and information technology (IT) systems). While exploration is most impacted by a learning culture, autonomy and IT systems, exploitation is closer related to collaborative leadership and learning culture.
Keywords: Automotive industry; Innovation; Knowledge exploitation; Knowledge exploration; Knowledge management